Fertility and Neonatal Outcomes of Freeze-All vs. Fresh Embryo Transfer in Women With Advanced Endometriosis - Wu, JIayi; Yang, Xiaoyan; Huang, Jiaan; Kuang, Yanping; Wang, Yun (Frontiers in Endocrinology, 2019)
BACKGROUND: Eutopic endometrium from women with endometriosis has functional changes in several aspects, which may largely account for the decrease in the quality of endometrial receptivity. It is of utmost importance to know whether freeze-all strategy can restore optimal receptivity in endometriotic women leading to the better ART outcomes. METHODS: Retrospective study involved patients with advanced endometriosis undergoing first embryo transfer cycles during the period from March 2006 to March 2017 at a tertiary care center. After propensity score matching, there were 506 women in the freeze-all group and 255 women in fresh group. Our main outcomes included the rates of implantation, clinical pregnancy and live birth. Subgroup analyses were performed after stratification by the number of oocytes retrieved and fertilization method. Neonatal outcomes included gestational age and birth weight z-score for singletons and multiple births. RESULTS: In our matched cohort, the implantation, clinical pregnancy and live birth rates were statistically significantly higher in the freeze-all group compared with fresh transfer groups (34.4 vs 25.5%, 51.8 vs 38.8% and 45.3 vs 31.8%, all P < 0.001, respectively) . A more beneficial effect of freeze-all cycles was found in patients who got more than 15 oocytes. Additionally, when ICSI insemination techniques were used to achieve fertilization, the advantage of freeze-all strategy was not obvious. Assessment of 382 babies showed no statistically significant difference in the mode of delivery, sex of live-born, gestational age, unadjusted median birth weight and z-score between two study groups. CONCLUSION: Freeze-all strategy is an attractive option to improve the outcomes of ART for women with advanced endometriosis.